Radiofrequency-assisted transection of the pancreas versus stapler in distal pancreatectomy: study protocol for a multicentric randomised clinical trial (TRANSPAIRE). Issue 11 (4th November 2022) - Sánchez-Velázquez, Patricia; Pueyo-Périz, Eva; Álamo, J M; Suarez Artacho, Gonzalo; Gómez Bravo, Miguel Ángel; Marcello, Manuel; Vicente, Emilio; Quijano, Yolanda; Ferri, Valentina; Caruso, Riccardo; Dorcaratto, Dimitri; Sabater, Luis; et al.
Abstract : Introduction: To date, no pancreatic stump closure technique has been shown to be superior to any other in distal pancreatectomy. Although several studies have shown a trend towards better results in transection using a radiofrequency device (radiofrequency-assisted transection (RFT)), no randomised trial for this purpose has been performed to date. Therefore, we designed a randomised clinical trial, with the hypothesis that this technique used in distal pancreatectomies is superior in reducing clinically relevant postoperative pancreatic fistula (CR-POPF) than mechanical closures. Methods and analysis: TRANSPAIRE is a multicentre randomised controlled trial conducted in seven Spanish pancreatic centres that includes 112 patients undergoing elective distal pancreatectomy for any indication who will be randomly assigned to RFT or classic stapler transections (control group) in a ratio of 1:1. The primary outcome is the CR-POPF percentage. Sample size is calculated with the following assumptions: 5% one-sided significance level (α), 80% power (1−β), expected POPF in control group of 32%, expected POPF in RFT group of 10% and a clinically relevant difference of 22%. Secondary outcomes include postoperative results, complications, radiological evaluation of the pancreatic stump, metabolomic profile of postoperative peritoneal fluid, survival and quality of life. Follow-ups will be carried out in the external consultation at 1, 6 and 12 months postoperatively. Ethics and dissemination: TRANSPAIRE has been approved by the CEIM-PSMAR Ethics Committee. This project is being carried out in accordance with national and international guidelines, the basic principles of protection of human rights and dignity established in the Declaration of Helsinki (64th General Assembly, Fortaleza, Brazil, October 2013), and in accordance with regulations in studies with biological samples, Law 14/2007 on Biomedical Research will be followed. We have defined a dissemination strategy, whose main objective is the participation of stakeholders and the transfer of knowledge to support the exploitation of activities. Registration details: ClinicalTrials.gov Registry (NCT04402346 ).